Study of Signal Transmission through different Array of Cu, Au and Ag Nanospheres (Journal of Nepal Physical Society, 2017)
Twenty first century is the age of Information Technology and we always look for faster information transport and processing capabilities. Data can be moved by transistors and optical fibers. Transistors carry small amount of data and are small in size while optical fibers can carry huge amount of data but are much bigger in size. Metal nanostructures may possess right combination of electric and optical properties to tackle the issues outlined above and realized the dream of significantly faster processing speeds. In this work, dispersion relation in Plasmon modes in linear chain and alternated chain of nanoparticles like silver-gold, silver-copper and gold-copper were studied. Expressions of angular frequency of Plasmon modes, group-velocity and extinction-coefficient were derived by solving equation of motion of Plasmon oscillation on the single kind of nanoparticle and that on different alternated chain of nanoparticles. Expressions of angular frequency of Plasmon modes, group velocity and extinction coefficient were tested for specific linear chain of nanoparticles. Extinction coefficients for the linear chain of Copper, gold and silver nanoparticles were found to be less and group velocities higher than that of alternated silver-gold and alternated gold-copper at their respective resonance frequencies.Journal of Nepal Physical SocietyVolume 4, Issue 1, February 2017, Page: 42-48